Evaluating the degree of weathering in landslide-prone soils in the humid tropics : the case of Limbe, SW Cameroon - Ernst, Gerald G. J. (2013)
This study analyses the behaviour and mobility of major and some trace elements during the physical and chemical development of landslide-prone soil profiles in Limbe, SW Cameroon. The soils result from in situ weathering of Tertiary basaltic and picrobasaltic rocks. Textural and chemical characterisations, together with two mass balance models are applied to understand the mobility and redistribution of elements during the weathering of pyroclastic cones and lava flows. Weathering indices are used to estimate the extent of weathering. The chemical composition of the samples is evaluated by Inductively Coupled Plasma–Optical Emission Spectroscopy (ICP–OES) and their mineralogical composition by X-Ray Diffraction (XRD) analyses. It is observed that intensive weathering results in thick meta-stable soils in which significant loss of Ca, K, Mg, Na and Sr has taken place. There is a noticeable relative enrichment in all analysed trace elements (Ba, Zr, Y, Sc, V, Ni, and Co). Ti, Fe, Al, Mn, P and Ce tend to be leached in some horizons and concentrated in others. Zr, Ti, and Ce concentrations are greater in the soils than in the bedrock but show slight fluctuations in the soil and saprolites hence cannot be used as immobile elements for mass balance evaluations. Y increases progressively with advanced weathering. Major secondary mineral phases developed through weathering are a mixture of expanding (smectites) and non-expanding clays (kaolinite, halloysite and mica). The profiles show the presence of textural heterogeneities that can be exploited as slip surfaces. Data plotted in Si–Al–Fe diagram point out that the most advanced stage of weathering noted in these profiles is the kaolinisation stage.